Peran Universitas dalam Mengurangi Food Loss dan Food Waste: Tinjauan Lintas Sektor di Sembalun, Nusa Tenggara Barat - Isnain, Fuad Sauqi; Saloko, Satrijo (Jurnal Informasi, Sains dan Teknologi, 2025)
Food loss and food waste (FLW) constitute systemic challenges in modern food systems, with direct implications for resource efficiency, environmental sustainability, and food security, particularly in developing countries where horticultural food loss persists upstream while food waste increases in downstream tourism sectors. This review synthesizes literature from 2015 to 2025 on horticultural food loss, tourism-related food waste, and the role of universities in cross-sectoral FLW reduction, using Sembalun, West Nusa Tenggara, as an illustrative agrarian–tourism landscape. The review is based on a multi-database search of academic sources (ScienceDirect/Elsevier, SpringerLink, Wiley Online Library, Taylor & Francis Online, MDPI, and Emerald Insight), complemented by key policy documents from FAO, UNEP, and UNWTO. Thematic synthesis indicates that upstream food loss and downstream food waste reflect structural mismatches between local production systems, tourism consumption patterns, and food governance, and therefore cannot be effectively addressed through isolated sectoral or technical interventions. The review highlights universities as strategic knowledge brokers that facilitate penta-helix collaboration, generate empirical evidence, and support the design of integrated interventions. This study underscores the need to strengthen universities' role in bridging agriculture, tourism, and policy to advance FLW reduction and support sustainable tourism development in rural destinations such as Sembalun, West Nusa Tenggara.